A student‐centred feedback model for educators. (11th March 2013) - Rudland, Joy; Wilkinson, Tim; Wearn, Andy; Nicol, Pam; Tunny, Terry; Owen, Cathy; O'Keefe, Maree
Summary Background: Effective feedback is instrumental to effective learning. Current feedback models tend to be educator driven rather than learner‐centred, with the focus on how the supervisor should give feedback rather than on the role of the learner in requesting and responding to feedback. Context: An alternative approach emphasising the theoretical principles of student‐centred and self‐regulated learning is offered, drawing upon the literature and also upon the experience of the authors. Innovation: The proposed feedback model places the student in the centre of the feedback process, and stresses that the attainment of student learning outcomes is influenced by the students themselves. This model emphasises the attributes of the student, particularly responsiveness, receptiveness and reflection, whilst acknowledging the important role that the context and attributes of the supervisor have in influencing the quality of feedback. Implications: Educational institutions should consider strategies to encourage and enable students to maximise the many feedback opportunities available to them. As a minimum, educators should remind students about their central role in the feedback process, and support them to develop confidence in meeting this role. In addition, supervisors may need support to develop the skills to shift the balance of responsibility and support students in precipitating feedback moments. Research is also required to validate the proposed model and to determine how to support students to adopt self‐regulatory learning, with feedback as a central platform.